DAMPAK FINANCIAL TECHNOLOGY, LITERASI KEUANGAN DAN FEAR OF MISSING OUT (FOMO) TERHADAP MINAT INVESTASI: PERAN KEMUDAHAN PENGGUNAAN SEBAGAI VARIABEL MODERASI - M Ainun Naim; Fakhmi Zakaria; Ariati Anomsari; Diana Puspitasari (Politeknik Negeri Ambon, 2026)
Introduction: The rapid development of digital transformation in the financial sector, known as financial technology, has provided broader access to financial services. Generation Z, as a generation that has grown up with digital technology, is highly susceptible to trends and psychological phenomena such as Fear of Missing Out (FOMO). In Semarang City, this trend is accompanied by an increase in the number of first-time investors; however, many novice investors still make investment decisions without adequate understanding due to limited financial literacy. Therefore, understanding the psychological and behavioral factors that influence investment interest among Generation Z, as well as the role of ease of use in these relationships, is essential.Methods: This study employed a quantitative approach with an explanatory research design. Data were collected through a survey of 120 Generation Z respondents residing in Semarang City who were interested in investing. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software to test the hypotheses and evaluate the validity and reliability of the research model, including the role of ease of use as a moderating variable.Results: The results show that financial technology, financial literacy, and FOMO have a positive and significant influence on investment interest among Generation Z in Semarang City. Financial technology facilitates access to and improves the efficiency of investment activities, financial literacy supports wiser investment decision-making, while FOMO encourages investment interest due to the desire to keep up with investment trends. Furthermore, ease of use positively moderates the effects of financial technology, financial literacy, and FOMO on investment interest. These findings highlight the importance of accessible digital platforms and financial knowledge in increasing investment interest among Generation Z.Keywords: Financial Technology; Financial Literacy; Fear of Missing Out; Ease of Use; Investment Interest.